Rapid Molecular Diagnosis of Extra-Pulmonary Tuberculosis by Xpert/RIF Ultra - Rindi, Laura (Frontiers in Microbiology, 2022)
Rapid detection of Mycobacterium tuberculosis complex and determination of drug resistance is essential for early diagnosis and treatment of tuberculosis (TB). Xpert MTB/RIF Ultra (Xpert Ultra), a molecular test that can simultaneously identify M. tuberculosis complex and resistance to rifampicin directly on clinical samples, is currently used. Xpert Ultra represents a helpful tool for rapid pulmonary TB diagnosis especially in patients with paucibacillary infection. The aim of the present review is to provide an overview of the diagnostic performance of Xpert Ultra for the detection of extra-pulmonary tuberculosis.